The Strategic Role of Competency Assessors in Ensuring Objectivity in Competency Certification: A Case Study of LSP-P1 of Sahid Polytechnic, Indonesia - Kadek Wira Adi Saputra; Suci Sandi Wachyuni; I Wayan Eka Sudarmawan (Politeknik Sahid, 2026)
This study aims to analyze the strategic role of competency assessors in maintaining the objectivity of competency certification based on the Indonesian National Work Competency Standards (SKKNI) at the First-Party Professional Certification Body (LSP P1) of Sahid Polytechnic in the era of the ASEAN Economic Community (AEC). This study employed a qualitative approach with a case study design. The informants consisted of 12 competency assessors, 2 LSP P1 administrators, and 5 certification candidates selected through purposive sampling. Data were collected through interviews, observations, and document analysis, and analyzed thematically using source and technique triangulation to ensure data credibility.The findings highlight the importance of assessor professionalism, integrity, and consistent certification governance in ensuring objectivity, and provide strategic insights for strengthening the quality of competency certification in vocational education.